The effects of spiritual wellbeing on life satisfaction in hematologic cancer patients aged 65 and older in Turkey: mediating role of hope - Turan, Guelcan Bahcecioglu; Ozer, Zulfunaz; Yanmis, Safiye (Wiley, 2024)
BackgroundThe mediating role of hope in the effects of spiritual wellbeing on life satisfaction in elderly haematologic cancer patients in Turkey was investigated in the present study.MethodsThe study was conducted in a descriptive, cross-sectional and correlational design. The study was conducted with 150 patients aged 65 and older who were diagnosed with haematologic cancer and who were referred to a university hospital haematology clinic and outpatient clinic. Research data were collected with Descriptive Information Form, Dispositional Hope Scale (DHS), Spiritual Well-being Scale (FACIT-Sp-12) and Satisfaction with Life Scale (SWLS).ResultsFACIT-Sp-12 score was 37.25 +/- 7.29; DHS score was 40.42 +/- 8.29, SWLS score was 16.24 +/- 8.79. FACIT-Sp-12 (beta = 0.668) and DHS (beta = 0.226) were found to affect SWLS positively. In terms of the effect of FACIT-Sp-12 on SWLS, DHS has a mediating role and makes the positive effect of FACIT-Sp-12 on SWLS stronger (beta = 0.771).ConclusionsSpiritual wellbeing levels of the participants in our study were found to be high, while their levels of satisfaction with life and hope were found to be moderate. It was also concluded that spiritual wellbeing had a direct effect on satisfaction with life and an indirect effect through the mediating role of hope.
Keywords: haematologic cancers; hope; nurse; older adults; satisfaction life; spiritual wellbeing